1981
DOI: 10.1007/bf00008269
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drought on benthic invertebrate communities in a lowland river

Abstract: Benthic macroinvertebrates were sampled at regular intervals from rural and urban sections of the River Roding, Essex, England, in 1975 and1976 . During the latter year a severe drought led to a marked decline in flows and to desiccation of parts of the river bed . In general, drought conditions resulted in an increase in invertebrate populations and possible reasons for this are presented . A considerable number of individuals of certain groups such as cased caddisfly larvae and prosobranch molluscs were, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 14 publications
3
68
0
6
Order By: Relevance
“…Collier and Quinn, 2003;Robinson et al, 2004) and short duration droughts (e.g. Hynes, 1958;Extence 1981;Ledger and Hildrew 2001;Lake, 2003). However, the recovery pattern associated with supra-seasonal droughts has not been widely reported (Lake 2003) and data demonstrating the extended duration of faunal recovery over two years were limited to a small number of sites until now (e.g., Wood et al, 2000;Wood and Armitage 2004;Wright et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Collier and Quinn, 2003;Robinson et al, 2004) and short duration droughts (e.g. Hynes, 1958;Extence 1981;Ledger and Hildrew 2001;Lake, 2003). However, the recovery pattern associated with supra-seasonal droughts has not been widely reported (Lake 2003) and data demonstrating the extended duration of faunal recovery over two years were limited to a small number of sites until now (e.g., Wood et al, 2000;Wood and Armitage 2004;Wright et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the impact of such a reduction in water level has been investigated for river invertebrate communities (Extence 1981, Chessman & Robinson 1987 and anadromous fish species (Heggenes et al 1996, Armstrong et al 1998, little consideration has been paid to the wider consequence of drought-induced reduction of freshwater flow on the distribution of estuarine invertebrates. investigated the effect of low flows on tidal freshwater macroinvertebrates at the head of an estuary, and noted dramatic changes in community composition with small increases in salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Although highly variable, the survival of invertebrates generally continued to decline with increased duration of exposure. Many studies have found losses of invertebrates caused by decreasing discharges from power generating plants causing stranding (Fisher and LaVoy 1972;Kroger 1973;Extence 1981;Corrarino and Brusven 1983) and desiccation (Powell 1958;Pearson et.al. 1968) of macroinvertebrates in shallow shoreline areas.…”
Section: Artificial Exposuresmentioning
confidence: 99%
“…Other invertebrates, such as the caddisfly Cheumatopsyche (Hydropsychidae family), have been found to persist or even flourish under hydropeaking discharges because they burrow into the substrate during lower water levels (Trotzky and Gregory 1974;Brusven and MacPhee 1976;Brusven and Trihey 1978;Ward and Short 1978). Extence (1981) also indicated that uncased (relatively mobile) caddisfly larvae were relatively resistant to stranding mortality. Our tile surfaces served only as a relative index of potential vertical movement and escapement from desiccation; however, natural substrate sampling would likely quantify this macroinvertebrate migratory component more accurately.…”
Section: Artificial Exposuresmentioning
confidence: 99%